Suppression of Pratylenchus brachyurus and soybean growth inoculated with arbuscular mycorrhizal fungus - Trentin, Edicarla; Portela, Valéria Ortaça; Schmitt, Juliane; Unfer, Reyllis Kiefer; Antoniolli, Zaida Inês; Jacques, Rodrigo Josemar Seminoti (Ciência e Natura, 2021)
Arbuscular mycorrhizal fungi perform a variety of plant-beneficial processes. including increased resistance to disease. The objective of this work was to study arbuscular mycorrhizal fungus Rhizoglomus clarum effect on phytonematode Pratylenchus brachyurus suppression and on soybean plants growth. Two experiments were performed under greenhouse conditions. First. soybean plants growth was evaluated in mycorrhizal fungi presence and absence. In the second experiment. phytonematode damage in soybean cultivated in mycorrhizal fungi presence and absence was evaluated. During soybean flowering was evaluated mycorrhizal colonization, dry matter, nodulation, chlorophyll and nutrient content in plant tissue, nematodes number in soil and root penetration, and nematode reproduction factor was obtained, R. clarum mycorrhizal colonization reduced by 64% the number of nematodes penetrated in roots and increased soybean plants nodulation, nutrient absorption and dry matter accumulation. The stimulation to mycorrhization is a strategy to reduce damage caused by Pratylenchus brachyurus to soybean plants.